Prescription trends and costs of diabetes medications in Australia between 2003 and 2019: an analysis and review of the literature. Issue 5 (10th May 2022) - Cieslik, Luke K.; Cresswell, Nikki R.; Fineberg, Daniel; Mariani, Justin A.; Patel, Hitesh C.
Abstract: Background: Since the turn of the century, the prevalence of diabetes mellitus in Australia has increased, primarily due to rising rates of Type 2 diabetes. Simultaneously, the landscape of diabetes medications has evolved significantly. The change in prescribing trends and public spending on diabetes medications within Australia during this period are not well defined. Aims: To establish the frequency and cost of dispensed diabetes medications in the Australian public healthcare system between 2003 and 2019. Methods: We performed a longitudinal nationwide observational study using data obtained from the Pharmaceutical Benefits Scheme (PBS) and Medicare Benefits Schedule websites, which contain information on frequency and spending of diabetes medications dispensed in Australia. Results: The total number of PBS‐subsidised prescriptions dispensed for diabetes increased from 5 218 690 in 2003 to 12 188 568 in 2019, and spending increased from 117 241 031 to 598 904 983. Of the non‐insulin agents, metformin was consistently the most frequently dispensed agent, with a rapid growth in metformin combination tablets. Dispensation of sulphonylureas and thiazolidinediones have declined, with a simultaneous increase in dipeptidyl peptidase‐4 inhibitors, sodium‐glucose co‐transporter 2 inhibitors and glucagon‐like peptide‐1 receptor agonists. Conclusions: Our data show a large growth in the use of diabetes medications between 2003 and 2019. The rapid growth in dispensing of drugs with proven cardiovascular and renal benefits reflect the evolving approach of diabetes treatment, from a historical approach targeting glycaemic control alone, to a modern individualised approach targeting specific co‐morbidities.